Analisis Putusan Pengadilan Negeri Baturaja Dalam Perkara Tindak Pidana Pencurian Studi Kasus Nomor: 333/Pid.B/2020/PN BTA terhadap Peraturan Mahkamah Agung Nomor 02 Tahun 2012 - Jumadi Jumadi; Indrajaya Indrajaya (Universitas Batanghari Jambi, 2023)
The issue of criminal law is widely discussed and in the spotlight, the public in general considers that it is very unfair if these minor cases threaten the punishment is not proportional to the value of the goods stolen by the perpetrator. So that the petty theft crime should be threatened with Article 364 of the Criminal Code which is guided by Supreme Court Regulation No.2 of 2012 must be applied with Article 362 of the Criminal Code. The reason why the judge did not use Article 364 of the Criminal Code and Supreme Court Regulation No.2 of 2012 was because in this case there was a repeat of the criminal act. The problem in this journal is the result of the Baturaja District Court's decision on theft cases with a light loss value. The research of this journal is Empirical legal research, which was initially researched as secondary data and then continued with research on primary data in the field. Meanwhile , The Supreme Court Regulation is a statutory regulation issued by the Chief Justice on judicial technical issues, especially in filling legal vacancies or against the enactment of an Act for which there has never been an organic regulation, whose structure resembles the structure of the composition of the Act that through the consideration of the judge at the Baturaja District court who examines and decides this case Article 364 of the Criminal Code cannot be applied with a speedy examination event guided by Supreme Court Regulation No. 2 of 2012 because the act committed by the perpetrator is a repeat of a criminal act, although in Supreme Court Regulation No.2 of 2012 there is no mention of exceptions to the act of repetition of a criminal act, but expressly it is regulated in the Memorandum of Understanding on the Implementation of the Application of the Prudential Limits on Minor Crimes and the Amount of Fines and the Application of Restorative Justice. So that the sentence of imprisonment for 1 year and 8 months is considered appropriate to be imposed on the perpetrator, even though from the perpetrator's side the verdict has not met the sense of justice.